Evaluation of medication changes following severe COVID-19 infection: a multicentre evaluation - Martin Shaw; Tara Quasim; Pamela MacTavish; Rakesh Kishore; Joanne McPeake; Ruth Forrest; Antoin Breslin; Fiona MacGregor; Alison Oprey (BMJ Open Respiratory Research)
Background Critically ill patients often experience several transitions of care following critical illness. Research has explored the challenges which patients have with medication management across these transitions. It is unclear whether patients admitted to critical care due to COVID-19 will have similar challenges. The aim of this study was to explore medication management in critical care survivors following severe COVID-19.Methods Between 3 and 7 months post hospital discharge, patients who had been admitted to critical care due to severe COVID-19 were invited to an established recovery service. During the clinic consultation a medication review was performed by a pharmacist. This included medicines reconciliation, assessing the appropriateness of each of the prescribed medications and identification of medication changes. We also assessed changes to pain management in the discharge period.Results In total, 78 patients had a full medication review available. Over 70% of patients were taking an increased dose of medicine or a new medicine at clinic. There was a significant overall increase in new medication during the clinic consultation, across different British National Formulary classifications (OR: 1.73 (95% CI: 1.28 to 2.34), p<0.001). Compared with pre critical care admission, there was a significant increase in the number of patients taking regular analgesia following severe COVID-19 infection (23 (29.5%) vs 39 (50%), p<0.001).Conclusion Following severe COVID-19, patients may require new or increasing doses of medicines. Ongoing review of these patients is crucial to ensure optimal outcomes.